PREDIKAT KEPEMILIKAN DALAM BAHASA INGGRIS: KAJIAN SEMANTIK (Predicative Possession in English:The Study af Semantics) - Sofian, Ayi (Balai Bahasa Sumatra Barat, 2017)
Aspects examined in this study are transformation of meaning semantic roles appear in the predicative possession of English. Meanwhile to study semantic meanings related to possessor and possessee in predicative possession sentences, the author uses the theory taken from Quirk (1973) Halliday, Cook, and Jackendoff (1972). The method used in the research is descriptive qualitative methods. The data were taken from British National Corpus. The data contain predicative possession sentences in English that include have, own, possess and belong to. The predicative possession transformation of the meaning in English is a follows: have,own, and possess verbs can mutually transformed using substitution method either for SVO, SVOA, SVOOC or SVOOCA patterns. The result shows that there are some data that can be well transformed and produced the same meaning and there are some data that cannot be transformed because it produces a different meaning. For belong to, the transformation of meaning was done by paraphrasing with the other verbs such as have, own, and possess.